Electrochemical and photovoltaic studies on water soluble triads: Metallosupramolecular self-assembly of ditopic bis(imidazole) perylene diimide with platinum(II)-, and palladium(II)-2,2′:6′,2-terpyridyl complex ions - Buyukeksi, Sebile Isik; Orman, Efe Baturhan; Sengul, Abdurrahman; Altindal, Ahmet; Ozkaya, Ali Riza (ELSEVIER SCI LTD, 2017)
1,6,7,12-tetrakis-(4-methoxyphenoxy)perylene-3,4,9,10-tetracarboxylic dianhydride was functionalized to possess imidazole ligating sites at the imide positions, namely N,N'-bis(3-propylimidazole)-1,6,7,12-tetrakis-(4-methoxyphenoxy)perylene diimide (PDI-1). By using metal ion-ligand coordination approach, self-assembly of newly synthesized ditopic ligand (PDI-1) with 2,2':6',2-terpyridyl-platinum(II) and/or-palladium(II) complex ions produced novel water soluble triads [(terpy)M(II)-(PDI-1)-M(II)(terpy)](NO3)(4), M(II) = Pt(II) (PDI-2), and Pd(II) (PDI-3), respectively. The isolated triads were characterized by FT-IR, 1D-NMR (H-1 NMR and C-13 DEPT NMR), 2D-NMR (H-1-H-1 COSY, H-1-C-13 HSQC, H-1-C-13 HMBC), MALDI TOF mass.and UV/Vis spectroscopy. Redox and electrochromic properties of the compounds have been identified by electrochemical, in situ spectroelectrochemical, and in situ electrocalorimetric measurements. The measurements showed that the novel chromophores display both a reduction and oxidation process, with considerably narrow electrochemical HOMO-LUMO band gaps in suitable solvents. The reduction of the novel compounds at modest potentials especially, makes these novel chromophores good electron acceptors. Net spectral changes between the blue, red or pink and green colours suggested that the novel compounds are suitable for application in electrochromic devices. Furthermore, the introduction of the square-planar Pt(II) and/or Pd(II)-terpyridyl units to the PDI core by 'coordination to the imidazole ends of the PDI moiety strongly influenced the performance of the photovoltaic devices. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Perylene diimide (PDI); Platinum; Palladium; Terpyridine; Solar cell; Photovoltaics; SOLAR-CELLS; TERPYRIDINE COMPLEXES; HIGHLY FLUORESCENT; SUPRAMOLECULAR POLYMERS; PHYSICAL-PROPERTIES; CHEMICAL-STRUCTURE; DESIGN; LIGANDS; POLYMERIZATION; SEMICONDUCTORS; Chemistry; Engineering; Materials Science